Algunes consideracions sobre la traducció de textos alemanys no actuals: el cabal onomàstic alemany medieval i el seu tractament. - Riutort, Macià Riutort i (Zeitschrift für Katalanistik, 2025)
The aim of this contribution is to propose guidelines by which Catalan forms can be created of the German medieval onomastic corpus, with a further task being that of proposing guidelines for the Catalanization of the German medieval culturemes, that is, for unified forms for medieval concepts of the German material, social and political culture, in order to avoid substitutive or approximate translations of these concepts. The final aim is the creation of a Catalan onomastic corpus containing the proposals for Catalan forms of the onomastic and cultural material of the German medieval.